Keefektifan Model Explicit Instruction dalam Pembelajaran Keterampilan Menulis Teks Eksposisi Siswa - Suci Indasari; Muhammad Saleh; Usman Usman (SOCIETIES: Journal of Social Sciences and Humanities, 2023)
Abstract.This study aims to determine the effectiveness of the explicit instruction model in learning the skills of writing exposition texts for the tenth graders of MAN 1 Sinjai Utara. This type of research is classified as experimental research. The approach used in this research is a quantitative approach. The design used in this study is a quasi-experimental design. The population in this study was the entire class X MAN 1 Sinjai Utara, totaling 207 students and the sample used was 25 students. The amount was determined by using purposive sampling technique. Data collection techniques in this study used writing tests, observations, interviews, and documentation. The data analysis technique used is descriptive test, normality test, homogeneity test, and hypothesis testing. The results of this study indicate that; (1) learning without using explicit instruction model in the students' exposition text writing skills is in the less skilled category with an average value of 58.6. (2) Learning by applying the explicit instruction model in students' exposition text writing skills is in the skilled category with an average value of 77.9. (3) The explicit instruction model is effectively applied in learning the writing skills of the tenth grade students of MAN 1 Sinjai Utara Keyword : Explicit Instruction, Eksposition Text